2011
DOI: 10.1192/bjp.bp.109.077172
|View full text |Cite
|
Sign up to set email alerts
|

Erving Goffman's Asylums 50 years on

Abstract: , in a recent book review in this journal, wrote that 'It is now nearly 50 years since the action-research sociologist Erving Goffman turned his insider-view daily notes into a devastating critique of the realities of mental hospital life. Back then, sociologists and psychotherapists were natural allies rallying to the flag of community psychiatry, united in opposition to the hegemonic medical model'. Now, however, according to Holmes 'all has changed. Neuropsychiatry rules; Asylums (1961) lies unread; the few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…Our lower incidence rates may indicate that only a small proportion of people with anxiety and panic disorders seen in primary care have the problem identified and recorded in their health care record, which suggests either under detection or reluctance to disclose or document anxiety disorders in this setting. Previous work has suggested that few people with milder symptoms of anxiety, such as those with mixed anxiety and depressive disorder, seek help from their GP for these symptoms, although they are attending on a regular basis for other reasons [25]. Community incidence rates of anxiety disorders from screening using psychiatric diagnostic interviews in large population surveys are more similar to the incidence rates found in our study, although with different sub-groups included, for example varying from 11.1/1000PYAR including anxiety and mixed affective disorders [26] to 1.57% for anxiety disorders including panic, phobias and generalised anxiety [9].…”
Section: Discussionmentioning
confidence: 99%
“…Our lower incidence rates may indicate that only a small proportion of people with anxiety and panic disorders seen in primary care have the problem identified and recorded in their health care record, which suggests either under detection or reluctance to disclose or document anxiety disorders in this setting. Previous work has suggested that few people with milder symptoms of anxiety, such as those with mixed anxiety and depressive disorder, seek help from their GP for these symptoms, although they are attending on a regular basis for other reasons [25]. Community incidence rates of anxiety disorders from screening using psychiatric diagnostic interviews in large population surveys are more similar to the incidence rates found in our study, although with different sub-groups included, for example varying from 11.1/1000PYAR including anxiety and mixed affective disorders [26] to 1.57% for anxiety disorders including panic, phobias and generalised anxiety [9].…”
Section: Discussionmentioning
confidence: 99%
“…Asylum is a work that facilitated the development of contemporary, communityorientated mental health practices or the process of deinstitutionalisation (Adlam et al 2012;Suibhne 2011). Goffman's polemics favour the humanisation of a dehumanised group of people.…”
Section: The Total Institution Theorymentioning
confidence: 99%
“…Here Goffman's concept of institutionalisation is draw to explore the erosion of autonomy in the day care setting. Goffman [20] explained that total institutions such as large commercial, industrial, or educational establishments differ where the provision of human needs are organised for the masses [20]. A day care centre does not reflect a total institution as such because the elders return home at night.…”
Section: Losing Autonomymentioning
confidence: 99%
“…Nonetheless, the day care centre shares some features with total institutions. There existed "house rules" that an individual was expected to conform to following admission [20]. Here the older participants participated in group life, could not leave without permission and were expected to engage in daily activities that were carried out in a group and were tightly regulated by staff.…”
Section: Losing Autonomymentioning
confidence: 99%
See 1 more Smart Citation